Quantitative weighted mixed weak-type inequalities for classical operators - Ombrosi, Sheldy Javier (2016)
We improve on several mixed weak type inequalities both for the Hardy-Littlewoodmaximal function and for Calderón-Zygmund operators. These type of inequalitieswere considered by Muckenhoupt and Wheeden and later on by Sawyer estimatingthe L1,∞(uv) norm of v−1T(fv) for special cases. The emphasis is made in provingnew and more precise quantitative estimates involving the Ap or A∞ constants ofthe weights involved.